Analisis SWOT Strategi Pengelolaan Reputasi PT. Cowboy Nusantara Jaya - Yuva Naila; S Bekti Istiyanto (Communications, 2019)
ABSTRACT The increase in the rate of demand for beef in Indonesia is not offset by an increase in beef production. These problems led to the establishment of many beef import companies, one of which was PT. Cowboy Nusantara Jaya. Tight business competition, makes this company need to design a strategic plan in managing the company's reputation. Reputation management is planned strategically so that the company can win the best position on the market. Reputation management is planned strategically so that the company can win the best position on the market. The purpose of this research is that the writer wants to explore the reputation management strategy carried out by PT. Cowboy Nusantara Jaya based on SWOT analysis. The method used by the author in compiling this study is descriptive qualitative. In this study the authors used two data sources namely primary and secondary. The author conducted in-depth interviews with three informants selected based on purposive sampling technique to obtain primary data. Whereas, the secondary data obtained by the writer is documentation techniques. The results showed that PT. Cowboy Nusantara Jaya has implemented several strategies in maintaining the reputation of the parent company well. As a subsidiary of PT. Suri Nusantara Jaya in the Central Java region, PT. Cowboy Nusantara Jaya continues to strive to prioritize customer satisfaction. Based on the SWOT analysis of PT. Cowboy Nusantara Jaya manages the reputation of the company by maintaining product quality, product availability, product prices, and easy and fast service innovations for its customers.